Attaining Sustainable Economic Growth in Bangladesh: Role of External Financial Means of Implementation - Uddin, Kazi Mohammed Kamal; Chowdhury, Munem Ahmad (Asian Journal of Economic Modelling, 2021)
Sustainable development is the goal of every nation. For this reason, achieving rapid and continuous economic growth is imperative and steps should be taken to play a strong role by identifying and accelerating the performance of the areas that affect it the most. This paper explores the role of external financial means of implementation (MoI) in amplifying the economic growth of Bangladesh for the period 1990-2018. Two thoughts are specifically canvassed here: Sole contribution of export and each of the other MoI in achieving higher economic growth; total export earning or the aggregate amount of other MoI, which contribute the most. Co-integrating relations are determined by ARDL Bound test as variables are stationary at different level. In the long run, economic growth increase by 0.60, 0.06 and 0.38 units for every 1 unit of export, FDI and ODA increase. Money earned from remittances plays an insignificant negative role in GDP due to lack of investment and inappropriate consumption during that period. Export play the most effective role to boost economic growth as it contributes 0.05% more than aggregate value of other MoIs. The solidity of the results has been confirmed through various diagnostic tests.